Breaking through : essays, journals, and travelogues of Edward F. Ricketts - Ricketts, Edward Flanders, 1897-1948 (University of California Press, 2006)
This unprecedented collection, featuring previously unpublished pieces as well as others for the first time in their original from, reflects the wide scope of Ricketts's scientific philosophical, and literary interests during the years he lived and worked on Cannery Row in Monterey, California.